Reinventing the supply chain life cycle strategies and methods for analysis and decision making - Schniederjans, Marc J. (FT Press, 2013)
Optimize supply chains throughout their entire lifecycle: creation, growth, maturity, and decline! Reflecting up-to-the-minute "in-the-trenches" experience and pioneering research, this book illuminates the complex transformational processes associated with managing complex supply chains that incorporate multiple products and services within ever-changing networks. Marc J. Schniederjans and Stephen B. Legrand walk you through: starting, creating, and building new supply chains; then, realigning those supply chains for growth, adjusting to dynamic change, readjusting networks, building flexibility, and managing new supply chain risks. Next, they offer practical, realistic guidance for realigning "mature" supply chains, innovating, controlling costs; and smoothly managing declining demand. Throughout, they offer invaluable insights and tools for negotiating, measuring performance, anticipating change, improving agility and flexibility, meeting commitments to social responsibility and the law; and much more. Based on the authors' up-to-the minute supply chain experience and pioneering academic research, Reinventing the Supply Chain Life Cycle contains many real-world examples and interviews with executives from some of the world's top organizations. It integrates content related to key certifications and offers valuable material that can be incorporated directly into existing supply chain practices, procedures, and policies.
Includes bibliographical references and index. - Print version record
Keywords: Business logistics; Strategic planning; Logistique (Organisation); Planification stratégique; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior